PENDAFTARAN HAK ATAS TANAH MELALUI PROGRAM NASIONAL AGRARIA (PRONA) TAHUN 2015 DI KABUPATEN AGAM (STUDI ATAS PELAKSANAAN PP NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - Anggun Lestari Suryamizon; Wendy Afandi (Ensiklopedia Social Review, 2021)
Initially, Prona was implemented based on the Decree of the Minister of Home Affairs No. 189 of 1981 concerning the National Agrarian Operations Project. The project is tasked with processing land certificates en masse as an embodiment of the Catur Orderly program in the land sector whose implementation is carried out in an integrated manner and is aimed at all levels of society, especially for the economically weak, as well as resolving completely strategic land disputes. From the above provisions, it is known that the Government's efforts to implement land order can be said to be maximal, we can see from the various legal products issued, the existence of the National Agrarian Program, an institution that specifically handles the land sector (National Land Agency), as well as competent legal institutions to resolve disputes. landKeywords: Registration, Land, Prona.